OPINION OF INTERNAL PARTICIPANTS ON INTERNAL CONSTRANTS OF DISKOMINFO BANGKA BARAT IN SUBMITTING INFORMATION THROUGH THE NEWS - Tri Oktaviani; Sepriadi Saputra (Jurnal Prodi Ilmu Komunikasi, 2022)
This research journal is entitled "Opinion of Internship Participants on Internal Constraints of Diskominfo West Bangka in Conveying Information through News". This study aims to describe the internal constraints of Diskominfo West Bangka in delivering information through news. This topic was chosen because the apprentices felt that it was not ideal, this condition made the West Bangka Discominfo need to be aware of and understand the obstacles experienced in conveying information so as to avoid the lack of coverage. The research method is descriptive and qualitative, through the researcher using data sources from interns as well as the authors of this study, using in-depth observations and interviews with three journalists from Diskominfo West Bangka. The results showed that the internal obstacles in the West Bangka Diskominfo were the lack of journalistic soft skills and the lack of human resources.